Algunas piezas de platería del siglo XIX en el noroeste de la provincia de Palencia: comarca de Guardo - Alonso Benito, Javier (Estudios humanísticos. Geografía, historia y arte, 1996)
The Guardo and his region silversmith works is quite unknown until now, as occured in many other trades in Spain. The study of some pieces of 19th century permited valuable insight in discovering the style and evolution that took place in this particular type of silverwork. In this region, during this time, models were found similar lo those discovered in other Spanish centers. One of the silvers more importants that made some pieces in the area was Manuel Rebollo, born in León, town were he worked.